Epidemiology of suicidal feelings in an ageing Swedish population: from old to very old age in the Gothenburg H70 Birth Cohort Studies. (2020) - Fässberg, M. M.; Vanaelst, B.; Jonson, M.; Sterner, T. R.; Ahlner, F.; Wetterberg, H.; Rydén, L.; Kern, S.; Sigström, R.; Zettergren, A.; Skoog, I.; Waern, M.
Abstract: Aims: The first aim of this study was to provide prevalence suicidal feelings over time (past week, past month, past year and lifetime) in a population-based sample of old to very old adults without dementia. Does prevalence change with rising age? The second aim was to examine the fluctuation of suicidal feelings over time. How does this coincide with depression status? Methods: Data were derived from the Gothenburg H70 Birth Cohort Studies (the H70 studies) which are multidisciplinary longitudinal studies on ageing. A representative sample of adults in Gothenburg, Sweden with birth years 1901–1944 were invited to take part in a longitudinal health study on ageing and participated at one or more occasions during 1986–2014. The sample consisted of 6668 observations originating from 3972 participants without dementia between the ages of 70 and 108, including 1604 participants with multiple examination times. Suicidal feelings were examined during a psychiatric interview using the Paykel questions (life not worth living, death wishes, thoughts of taking own life, seriously considered taking life, attempted suicide). Results: Prevalence figures for suicidal feelings of any severity were as follows: past week 4.8%, past month 6.7%, past year 11.2% and lifetime 25.2%. Prevalence rates increased with age in the total group and in women but not in men. Suicidal feelings were common in participants with concurrent major or minor depression, but over a third of the participants who reported suicidal feelings did not fulfil criteria for these diagnoses nor did they present elevated mean depressive symptom scores. The majority of participants consistently reported no experience of suicidal feelings over multiple examination times, but fluctuation was more common in women compared with men. Conclusion: Suicidal feelings in late-life are uncommon in individuals without depression indicating that such behaviour is not a widespread, normative phenomenon. However, such feelings may occur outside the context of depression.